Seneca Valley Virus 3Cpro Cleaves Heterogeneous Nuclear Ribonucleoprotein K to Facilitate Viral Replication - Song, Jiangwei; Quan, Rong; Wang, Dan; Liu, Jue (Frontiers in Microbiology, 2022)
Seneca Valley virus (SVV) has emerged as an important pathogen that is associated with idiopathic vesicular infection in pigs, causing potential threat to the global swine industry. The heterogeneous nuclear ribonucleoprotein K (hnRNP K) that shuttles between the nucleus and cytoplasm plays an important role in viral infection. In this study, we observed that hnRNP K was cleaved and redistributed in the cytoplasm after SVV infection. In fact, hnRNP K is degraded during SVV infection, and viral 3C protease (3Cpro) is necessary for its cleavage, degradation, and redistribution. Further studies identified that 3Cpro cleaves and degrades hnRNP K depending on its protease activity, the degradation via caspase pathway which attenuated in the presence of a caspase inhibitor, Z-VAD-FMK. SVV 3Cpro cleaved hnRNP K at residue Q364, and expression of cleavage fragment hnRNP K (aa.365–464) facilitates viral replication, which is similar to full-length hnRNP K, whereas hnRNP K (aa.1–364) inhibits viral replication. Additionally, hnRNP K interacts with the viral 5′ untranslated region (UTR), and small interfering RNA (siRNA)-mediated knockdown of hnRNP K results in significant inhibition of SVV replication. Overall, our results demonstrated that SVV 3Cpro targets hnRNP K for cleavage, degradation, and redistribution, which is beneficial for SVV replication. The finding provides a novel antiviral strategy to utilize hnRNP K as a potential target for therapy.